2023
DOI: 10.1002/glia.24327
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of a functional astrocyte syncytium in the developing mouse hippocampus

Abstract: Astrocytes are increasingly shown to operate as an isopotential syncytium in brain function. Protoplasmic astrocytes acquire this ability to functionally go beyond the single‐cell level by evolving into a spongiform morphology, cytoplasmically connecting into a syncytium, and expressing a high density of K+ conductance. However, none of these cellular/functional features exist in neonatal newborn astrocytes, which imposes a basic question of when a functional syncytium evolves in the developing brain. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Here, the rapid exchange of K + with neighboring cells is taken as a measure of the coupling strength of a given astrocyte. Previous reports established that the degree of depolarization of a given astrocyte induced by the K + -free pipette solution is inversely correlated to tracer coupling with neighboring cells (Zhong et al, 2023), which was roughly confirmed here. Our results confirm the applicability of this approach in cortical layer II/III astrocytes.…”
Section: Probing Astrocytic Gap Junctional Couplingsupporting
confidence: 88%
“…Here, the rapid exchange of K + with neighboring cells is taken as a measure of the coupling strength of a given astrocyte. Previous reports established that the degree of depolarization of a given astrocyte induced by the K + -free pipette solution is inversely correlated to tracer coupling with neighboring cells (Zhong et al, 2023), which was roughly confirmed here. Our results confirm the applicability of this approach in cortical layer II/III astrocytes.…”
Section: Probing Astrocytic Gap Junctional Couplingsupporting
confidence: 88%
“…We adjusted the amount of AAV injected to obtain a sparse astrocyte labelling, and we focused our analyses of the effects of astrocyte APP KD on hippocampus and cortex. In addition, given the role of APP in the developing brain, we confined our analyses to P21 when the bulk of synapse formation had occurred and when astrocytes had been segregated from each other to form their characteristic individual domains and reached a mature complex morphology (Bushong et al, 2004; Saint-Martin and Goda, 2022; Zhong et al, 2023). To confirm astrocytic APP KD in vivo , P21 brain sections were processed for immunohistochemistry to label for APP and imaged on a confocal microscope (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptomic analysis ( Zhang et al, 2016 ), physiology studies ( Oberheim et al, 2009 ), as well as histological characterization of human and mouse brains ( Degl’Innocenti et al, 2022 ), have pointed out the overexpression of species-specific elements correlated to calcium-operated signal transduction. Calcium signals propagate in the astrocytic syncytia through gap junctions ( Verkhratsky and Kettenmann, 1996 ), whose functionality has been assessed in rodent models ( Zhong et al, 2023 ). At present, no correspondent investigations have been conducted in human samples and the electrophysiological properties of human astrocytic syncytia remain an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Gap junctions mediate the connection between neighboring astrocytes within syncytia, an element that is not only structural but also serves to guarantee the spatial redistribution of K + and Na + ions, as well as of nutrients, metabolites, and signaling molecules for the coordination of neuronal activity and brain energy metabolism ( Ma et al, 2016 ). In the mouse, gap junction coupling by means of connexins 30, 43 and 26 appears to be pivotal for the establishment of syncytia ( Dermietzel et al, 1989 ; Charvériat et al, 2021 ), which have been shown to acquire maturation only postnatally (P15) ( Zhong et al, 2023 ). Evidence suggests that human astrocytes also exhibit gap junction coupling ( Bedner et al, 2015 ), as well as connexin 43 ( Aronica et al, 2001 ), and connexin 30 ( Nagy et al, 1999 ).…”
Section: Molecular and Functional Characterization Of Human And Mouse...mentioning
confidence: 99%